Contribution of community pharmacists in educating the asthma patients - Hamoud Saud Alotaibi; Thippeswamy Boreddy Shivanandappa; Sivagurunathan Nagarethinam (Elsevier, 2016)
Background: In asthma, the preventive measures taken by patients play an important role in improving life span and quality of life. This can be done more efficiently by community pharmacist by providing patient counseling and improving knowledge of patient about disease, risk factors, medication management and preventive measures to control asthma. Objectives: The objective of the study was to evaluate the contribution of community pharmacists in improvement of life span and quality of life of asthma patients. Method: The study was performed from Mid September to Mid-November 2014 in Dawadmi, Riyadh province, KSA. Data were collected by using a structured face to face questionnaire with randomly selected different community pharmacies. The questionnaire composed of different closed questions about the action plan of pharmacists in asthma management and factors that affect the counseling of asthma patients by the pharmacists. Results: It is noteworthy to observe that, in general, pharmacists are sufficiently knowledgeable and competent to counsel their asthma patients effectively.